Cultural complex for the promotion and development of interculturality in Tacna - Alfaro Calumani, Pedro Donie (2014)
Objective: This research develops the proposal called: Architectural Cultural Complex Project for the promotion and dissemination of culture and intercultural population in Tacna. Method: The design was used descrptivo used in step information and data collection and served for a diagnosis. Then the experimental design allowed the extent to which the proposal is crucial in relation to cultural activities was used. Results: Tacna Region to establish itself as a tourist center, Commercial, Cultural and Recreational Eco national level, with a population identified with its historical legacy and cultural heritage; demand for infrastructure for informational, educational, cultural, social and economic events; reason which is required to provide it with a receiver and promoter of civic, cultural and recreational events center. It is noteworthy that the geopolitical and strategic location in the region and the city plays an important role, it will make possible a cultural and social exchange at local, national and international level. reason Conclusions: The problem of the lack of a receptor and promoter of civic, cultural and recreational events center, by lack, limitations and deficiencies of the infrastructure responsible for meeting the demand for local, national population and floating population provided evidence national and international. Why a cultural complex for the promotion and development of multiculturalism in Tacna is proposed.